Selective activation of four quasi-equivalent C–H bonds yields N-doped graphene nanoribbons with partial corannulene motifs - Gao, Yixuan; Huang, Li; Cao, Yun; Richter, Marcus; Qi, Jing; Zheng, Qi; Yang, Huan; Ma, Ji; Chang, Xiao; Fu, Xiaoshuai; Palma, Carlos-Andres; Lu, Hongliang; et al. (Nature Communications, 2022)
Selective C–H bond activation is one of the most challenging topics for organic reactions. The difficulties arise not only from the high C–H bond dissociation enthalpies but also the existence of multiple equivalent/quasi-equivalent reaction sites in organic molecules. Here, we successfully achieve the selective activation of four quasi-equivalent C–H bonds in a specially designed nitrogen-containing polycyclic hydrocarbon (N-PH). Density functional theory calculations reveal that the adsorption of N-PH on Ag(100) differentiates the activity of the four ortho C(sp3) atoms in the N-heterocycles into two groups, suggesting a selective dehydrogenation, which is demonstrated by sequential-annealing experiments of N-PH/Ag(100). Further annealing leads to the formation of N-doped graphene nanoribbons with partial corannulene motifs, realized by the C–H bond activation process. Our work provides a route of designing precursor molecules with ortho C(sp3) atom in an N-heterocycle to realize surface-induced selective dehydrogenation in quasi-equivalent sites.
CRIS-Team Scopus Importer:2023-03-20